A Qualitative Study of Fungi Adhered to some Aquatic Plants in Baghdad, Al-jadriya - Mohammad, Teeba H.; Taha, Zahraa R.; Hamad, Sumaya F.; Salim, Duha Hameed; Khajeek, Tamara Rafi (Iraqi Journal of Science, 2025)
A study was conducted on water's physical and chemical properties at five sites along the water channel within the University of Baghdad in Baghdad's Al-Jadriya district. All sites drew water from the Tigris River, adjacent to the university. The present study aimed to determine aquatic plant types inhabiting the study area and the diversity of fungi associated with these plants and fungi present in water during three seasons of the year: spring, autumn, and winter (2022 - 2023), considering five locations.The results of the current study showed that the water became alkaline and the oxygen level was good, four types of aquatic plants were diagnosed and isolated from the aqueducts that derive their water from the Tigris River: Ceratophyllum demersum, Najas marina, Hydrilla verticillata, and Lemna minor (duckweed). Also diagnosed 1141 fungal isolates belonging to 23 families were acquired. The family Trichocomaceae had the highest percentage at 21.42%, followed by Pleosporaceae and Mucoraceae with 9.52 % and 7.14 %, respectively. The families Saprolegniaceae and Nectriaceae also recorded significant rates. The result found the presence of forty-two fungal species, which include Aspergillus niger and A. Terreus, which had the very best appearance percentage in the collected water samples. This indicates an excessive level of fungal biodiversity in the study area because of favorable environmental situations for fungal increase. Furthermore, 255 fungal isolates were isolated from aquatic plants belonging to fourteen families. The Trichocomaceae family had the highest percentage at 16.6%, followed by 11.11% of Pleosporaceae and Chaetomiaceae families. The study also diagnosed 18 fungal species, Aspergillus niger, and A. Flavus, which had the highest percentage of appearance compared to other species collected. The important intention of this study was to conduct a qualitative assessment of the fungal families and the type of aquatic plants accrued from the Tigris River in Baghdad's Al-Jadriya district. This study also aimed to identify the aquatic flora to apprehend the biodiversity of fungi and plant life in the study area.